Is Antenatal Group B Streptococcal Carriage a Predictor of Adverse Obstetric Outcome?. Issue 3 (2000) - Garland, Suzanne M.; Kelly, Nigel; Ugoni, Antony M.
Abstract : Objectives: While early-onset neonatal GBS sepsis is positively associated with premature birth and prolonged rupture of membranes, there is debate in the literature as to whether maternal GBS colonization is a predictor of adverse obstetric outcome. This is a critical issue to resolve for appropriate management (expectant vs. interventional management) of the patient presenting with premature rupture of membranes, who has no overt signs of sepsis, but who is colonized with GBS. Methods: Since 1981 it has been hospital policy to screen all public patients antenatally for genital carriage of GBS by collection of a low vaginal swab at 28–32 weeks. All patients colonized with GBS antenatally are given penicillin as intrapartum chemoprophylaxis. Review of all GBScolonized antenatal patients for a 12-month period (580 of 4, 495 patients) and a randomized (every fourth consecutive antenatal patient) number of noncolonized patients (958) was made. Lower vaginal GBS colonization and other risk factors for preterm delivery were assessed using univariate and multivariate generalized linear modeling. Results: In the study group, the maternal GBS colonization rate was 12.9%. When cofounding variables were controlled in a multivariate analysis, the association between antepartum GBS colonization and preterm labor and preterm rupture of membranes was not significant. Conclusion: Maternal antenatal carriage of GBS does not predict preterm labor. Therefore it is appropriate that expectant management occur for a GBS-colonized woman who ruptures her membranes, is not in labor, and has no evidence of sepsis. Infect. Dis. Obstet. Gynecol. 8:138–142, 2000.